Failures East and West : cultural encounters between East Asia and Europe - Hertel, Ralf, 1973-; Sandrock, Kirsten A. (Edinburgh University Press, 2023)
Bringing together scholars working across Chinese Studies, Japanese Studies, English Studies and French Studies, this book presents new perspectives on instances of failed intercultural encounters by theorizing epistemologies of failure.
Keywords: Cultural relations in literature.; Failure (Psychology) in literature.; Europe -- Relations -- East Asia.; East Asia -- Relations -- Europe.; Relations culturelles dans la littérature.; Échec dans la littérature.; HISTORY / Asia / General; Cultural relations in literature; Failure (Psychology) in literature; International relations; East Asia; Europe